ANALISIS KINERJA KEUANGAN PADA PERUSAHAAN INDUSTRI FARMASI TAHUN 2017-2021 YANG TERDAFTAR DI BURSA EFEK INDONESIA - Septiani, Indri; A.M, Andi Ismatul Aulia (Universitas Patria Artha, 2023)
This study aims to determine the financial performance of pharmaceutical companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The type of research used in this research is quantitative data analysis. Data collection uses secondary data obtained from financial statements taken through the Indonesian stock exchange. The population and samples were taken based on certain criteria or purposive sampling. The results of the study can be concluded that when viewed in terms of the Liquidity ratio, PT Kalbe Farma Tbk is the company with the best liquidity ratio when compared to other companies sampled in this study, from the solvency ratio, PT Darya Victoria Laboratoria, Tbk is the best and best in terms of profitability ratios PT Kalbe Farma, Tbk is the best in generating profits.